Classifiers : a typology of noun categorization devices - Aĭkhenvalʹd, A. I͡U. (Aleksandra I͡Urʹevna) (Oxford [England] ; New York : Oxford University Press, 2000)
This text offers a cross-linguistic account of classifiers. Its range of exemplification includes major and minor languages from every continent and several of the examples are from the author's own fieldwork.
Noun class and gender systems -- Noun classifiers -- Numeral classifiers -- Classifiers in possessive constructions -- Verbal classifiers -- Locative and deictic classifiers -- Different classifier types in one language -- Multiple classifier languages -- Classifiers and other grammatical categories -- Semantics of noun categorization devices -- Semantic organization and functions of noun categorization -- Origin and development of noun categorization devices -- Noun categorization devices in language acquisition and dissolution -- Conclusions -- Appendix 1: Noun categorization by means other than classifiers -- Appendix 2: From nouns to classifiers : further examples of semantic change -- Appendix 3: Fieldworker's guide to classifier languages -- List of languages -- List of language families, linguistic areas, and proto-languages.
Second series statement from jacket.
Includes bibliographical references (pages 452-487) and indexes.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Keywords: Classifiers (Linguistics); Categorization (Linguistics); Grammar, Comparative and general -- Noun; Classificateurs (Linguistique); Catégorisation (Linguistique); Nom (Linguistique); LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Semantics; Categorization (Linguistics); Classifiers (Linguistics); Grammar, Comparative and general -- Noun; Classifiers (taalkunde); Naamwoorden; Taaltypologie